PENGUATAN KARAKTER MELALUI ROLE MODEL WIRACARITA SIJELLO TO MAMPU DENGAN PENDEKATAN PEMBELAJARAN MENDALAM PADA SISWA SEKOLAH DASAR - Lilis Septiani Lista; Andi Srimularahmah; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Muhammad Asdar; A. Nurhabibi Marwil; Sri Wahyuni Putri; A. Milasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is an important aspect of elementary education in the era of Society 5.0. However, the Bone Regency Education Report Card, 2023 showed a decline in student discipline, responsibility, and respect, with only 40% of students consistently demonstrating positive character behavior. This study aims to design and implement the Sijello to Mampu Puzzle as an interactive learning medium to strengthen the character values ​​of elementary school students. This study used the R&D method with the ADDIE model. Data were collected using pre-tests, post-tests, questionnaires, interviews, and observation sheets. Quantitative data were analyzed using descriptive statistics and paired t-tests, while qualitative data were analyzed thematically. The results showed that the developed puzzle media achieved a validity score of 87.5% (very valid), a practicality score of 85.2% (very practical), and an effectiveness score of 82.7% (effective).